Pendampingan Akuntansi dan Pajak Usaha Mikro, Kecil, dan Menengah (UMKM) di Gapoktan Lestari - Avisenna Harkat; Arisona Ahmad; Oryza Ardhiarisca; Dessy Putri Andini; Rahma Rina Wijayanti (Journal of Community Development, 2022)
This community service activity aims to assist farmer groups who are members of the Lestari Gapoktan in preparing financial information. Knowledge and skills in compiling financial information require an understanding of accounting. The resulting output target is the acquisition of accounting knowledge and skills to collect financial information, both manually and computerized. The next target is the use of financial information to calculate MSME taxes by PP RI No.23 of 2018 and the interests of applying for credit to financial institutions, photos of activities, one article in electronic mass media. The implementation method of this service is carried out by capturing the needs of Gapoktan Lestari as MSMEs in terms of financial administration in the form of discussion and question and answer activities. Furthermore, following up the conditions obtained by carrying out accounting bookkeeping assistance in training. The results of this service activity are the delivery of accounting knowledge; simple bookkeeping excels soft program files, publications in mass media, and activity photo files.